Proceso de atención de enfermería en paciente con obstrucción intestinal - Merlyn Alexandra, Medina De La Cruz (2018)
The intestinal obstruction is a pathology that occurs by the complete and persistent arrest of the intestinal transit at some point of the digestive tract. In the intestinal obstruction we have two clinical pictures which we have to know how to differentiate; mechanical obstruction when there is an obstacle to the passage of intestinal content, and paralytic ileus which consists of a compromise of the transit without a mechanical cause that justifies it, for which reason it is attributed to a motor alteration of the intestine. Intestinal obstruction can occur at any stage of life; the causes may vary according to the age group. However, the condition is more frequent in the fourth and fifth decades of life, although in the last 65 years the most frequent cause of obstruction has changed. 80% of intestinal obstructions occur in the small intestine and the rest in the colon. The signs and symptoms that occur depend on the location and cause of the intestinal obstruction, the most common are; vomiting, writhing, abdominal distension and alterations of the intestinal rhythm. Blood tests, plain abdominal radiography and abdominal ultrasound are used to diagnose intestinal obstruction. The treatment used in this pathology will depend on the complexity of the case, it can be treated with enemas, antibiotherapy and surgery. This case study deals with a patient who comes to the emergency area due to pain at the level of the mesogastrium, emesis, abdominal distension and absence of stool and flatus. In this case I focus on satisfying the patient's needs in relation to the symptomatology that the patient presents, so that nursing interventions are implemented for a satisfactory recovery.